The King of Crows : a Diviners novel - Bray, Libba (Atom, Great Britain, 2020)
Led by a vision, the Diviners travel to Bountiful, Nebraska, where they must confront their greatest fears and learn to rely on one another in order to save the world from catastrophe.
Keywords: Dead Fiction; Devil Fiction; Fantasy fiction